2017
DOI: 10.4236/aid.2017.72005
|View full text |Cite
|
Sign up to set email alerts
|

New Osteological Data on Malaria in Sardinia from Antiquity to the Modern Era

Abstract: Malaria has been an important disease throughout the history, particularly in the Mediterranean. The island of Sardinia (Italy) was characterized by severe endemic malaria from antiquity until its eradication in 1950. It provides an exceptional and unique site to examine the history of the disease and its effects on human biology and ecology. Endemic malaria can cause chronic hemolytic anemias that may result in osteological signatures. This paper examines these markers, Porotic Hyperostosis (PH) and Cribra Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The authors have indeed argued that this area was surrounded by marshes during the Roman period (83). An osteological study conducted in Sardinia for the so-called "malaria signature" on 283 skeletons dating from 4,700 BC to 1582 AD, supported the possible introduction of malaria by Carthaginians during the 6th to 3rd century BC (84). Porotic hyperostosis is the consequence of thalassemia resulting in an overgrowth of the spongy marrow space of the skull.…”
Section: Paleopathologymentioning
confidence: 99%
“…The authors have indeed argued that this area was surrounded by marshes during the Roman period (83). An osteological study conducted in Sardinia for the so-called "malaria signature" on 283 skeletons dating from 4,700 BC to 1582 AD, supported the possible introduction of malaria by Carthaginians during the 6th to 3rd century BC (84). Porotic hyperostosis is the consequence of thalassemia resulting in an overgrowth of the spongy marrow space of the skull.…”
Section: Paleopathologymentioning
confidence: 99%
“…In the example of the anthropological material of a Greek colonial population from the 5th to 3rd centuries bce , Keenleyside and Panayotova (2006) showed that nutritional deficiencies, thalassemia, sickle cell traits, and exposure to infectious diseases such as malaria could play an equal role in the development of the above‐mentioned skeletal lesions that can be pathognomonic skeletal signs in malaria. Interestingly, cribra orbitalia or cribra crania was found in high prevalence in medieval age cemeteries in Sardinia, but not in the Bronze Age and Roman and rarely in Neolithic sites (Tognotti et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%